HUBUNGAN TEKNIS AGRONOMI PELIBURAN TANAMAN JERUK SIAM BANJAR (Citrus reticulata) DENGAN WAKTU PEMATANGAN BUAH BERDASARKAN TIPE LUAPAN DI KABUPATEN BARITO KUALA - Karina Citra Dewi; Gusti Rusmayadi; Dewi Erika Adriani (EnviroScienteae, 2021)
Peliburan is a term, that raised up the mud from the channels to the mound (called tukungan/guludan in local language) or raise beds as one of agronomic technics based on local indigenous of tidal swamplands farmers in South Kalimantan. Peliburan has many benefits for Siam Banjar citrus plant, namely creating a suitable microclimate so that it might be used to determine the appropriate time for ripening and harvesting of citrus fruits. The objectives of this study were to: 1) Determine the effect of  peliburan on ripening time of Siam Banjar citrus fruit based on the type of overflow in Barito Kuala Regency, 2) Determine the joint or simultaneous effect, and partial effect of peliburan on ripening time of the Siam Banjar citrus fruit in Barito Kuala Regency 3) Determine the direct effect of peliburan on ripening time of Siam Banjar citrus fruit in Barito Kuala Regency.     The recent study  used survey and observation methods. The research location was chosen in purposive sampling method by considering the type of overflow and farmers as respondents in the selected villages with high productivity of Siam Banjar citrus. The study was conducted in four district in Barito Kuala Regency, namely Mandastana District, Belawang District, Cerbon District and Barambai District. The data analysis used to determine the effect of Peliburan was multiple regression analysis with a dummy variable consisted of 7 variables, namely X1 : time of peliburan,  X2 :  shape of peliburan, X3 : diameter of peliburan (cm), X4 : height of peliburan (cm), X5 : spacing between peliburan (population), X6 : age of peliburan (years) and X7 : Soil temperature (oC).            The results showed that agronomic technics that is shape of peliburan, height of peliburan, spacing between peliburan and soil temperature had an effect on ripening time of Siam Banjar citrus fruit both at type A and type B overflow in Barito Kuala Regency. Simultaneously, all independent variables of peliburan had a significant linear relationship with the dependent variable that is ripening time of Siam Banjar citrus fruit in Barito Kuala Regency. Partially, at type A overflow, time of peliburan, diameter of peliburan, spacing between peliburan , height of peliburan, and soil temperature had a significant effect, whereas at type B overflow, time of peliburan, diameter of peliburan, height of peliburan, spacing between peliburan and age of peliburan  had a significant effect on ripening time of Siam Banjar citrus fruit. The dominant direct effect of peliburan at type A and type B overflow was the soil temperature and height of peliburan.